Use of an Effective Attenuation Coefficient Value and Material Filter Technique for Scatter Correction in Tc-99m SPECT - Sayed, Inayatullah Shah; Muda, Siti Zubaidah (MEACSE Publications, 2016)
Accuracy in the diagnosis of disease in Tc-99m Single Photon Emission Computed Tomography is reduced due to the presence of scattered gamma photons in the image data. A range of scatter correction techniques exist, however, none is considered as the standard. The objective of this study is to apply a flat sheet of Aluminum 0.3mm thick as an absorber for the removal of scattered gamma photons and compare the image quality with those images obtained by using effective attenuation coefficient value. Data were acquired with the gamma camera (Philip ADAC Forte dual head) installed with LEHR collimator. A cylindrical phantom with cold and hot regions insert was scanned. Tc-99m radioactive material was introduced into the phantom. Images were reconstructed by using filtered back projection method. Perceived image quality and contrast of cold and hot regions, whereas, count profile and standard deviation in the count density of uniform region was measured. Quantitative analysis of all image quality parameters investigated show fair improvement with material filter. In conclusion, 0.3mm thickness of aluminum material filter may have some advantage over the use of effective attenuation coefficient value for scatter compensation when applied by scanning other ECT phantoms using Tc-99m radionuclide.